Journey of the glenoid in anatomic total shoulder replacement. (April 2019) - Castagna, Alessandro; Garofalo, Raffaele
Anatomic total shoulder arthroplasty (TSR) has been shown to generate good to excellent results for patients with osteoarthritis and a functioning rotator cuff. Many studies have reported that the glenoid component loosening and failure remain the most common long-term complication of total shoulder arthroplasty. The approach to glenoid component is critical because a surgeon should consider patient-specific anatomy, preserving bone stock and joint line restoration, for a good and durable shoulder function. Over the years, different glenoid design and materials have been tried in various configurations. These include cemented polyethylene, uncemented metal-backed and hybrid implants. Although advances in biomechanics, design and tribology have improved our understanding of the glenoid, the journey of the glenoid component in anatomic total shoulder arthroplasty has not yet reached its final destination. This article attempts to describe the evolution of the glenoid component in anatomic TSR and current practice.